Pemberian Kompos Azolla microphylla pada Pertumbuhan Bibit Karet (Hevea brasiliensis) Okulasi - Indriati Meilina Sari; Sampoerno Sampoerno; M. Amrul Khoiri (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2015)
This research aimed to study the effect of the Azolla microphylla compost on thegrowth of PB-260 clone rubber seedlings mini stump. This research has beenconducted atAgriculture Faculty, University of Riau starting from April to July 2013. The research wascarried out experimentally using completely randomized design non factorial consisting of4 treat ments and 3 replications, obtained 12 experimental units and each unit consists of3 seeds so that total earned is 36 rubber seedlings and as sample 2 seedlings per unitexperiment. Compost treatment given to the provision of treatment levels; 0, 15, 30 and45 g/polybag (0, 10, 20 and 30 ton/ha) mixed by weighing soil 3 kg (polybag size 20 cmx 40 cm). The data were statistically analyzed using ANOVA, followed by DNMRT at thelevel of 5%. Parameters observed are lenght of grafting (cm), stem graft girth (cm),number of leaves (sheet), leaf area (cmÂ²) and shoot root ratio (g). Giving A. microphyllacompost on growing mini stump rubber seedling significantly effect on extending the graftand number of leaves. Meanwhile, for stem graft girth, leaf area and shoot root ratio revealnot significant. Compost dosing 30 g/polybag shows the best results for the growth ofrubber seedlings mini stump compared them 0, 15 and 45 g/polybag